2018
DOI: 10.1136/bmjopen-2017-019039
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac implant registries 2006–2016: a systematic review and summary of global experiences

Abstract: ObjectivesThe importance of Cardiac Implant Registry (CIR) for ensuring a long-term follow-up in postmarket surveillance has been recognised and approved, but there is lack of consensus standards on how to establish a CIR. The aim of this study is to investigate the structure and key elements of CIRs in the past decade (2006–2016) and to provide recommendations on ‘best practice’ approaches.Settings and participantsA systematic search on CIR was employed in line with the Preferred Reporting Items for Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…As confirmed by data derived from AIAC Registry [5][6][7][8][9][10][11][12], the rise in ICD utilization was mostly due to the increased number of patients treated for primary prevention. Despite the absolute number of patients with diagnosis of VT/VF (extrapolated by Table 2), increased, the proportion of patients treated for secondary prevention dramatically dropped from 2001 to 2017.…”
Section: Implantable Cardioverter-defibrillatorsmentioning
confidence: 83%
See 1 more Smart Citation
“…As confirmed by data derived from AIAC Registry [5][6][7][8][9][10][11][12], the rise in ICD utilization was mostly due to the increased number of patients treated for primary prevention. Despite the absolute number of patients with diagnosis of VT/VF (extrapolated by Table 2), increased, the proportion of patients treated for secondary prevention dramatically dropped from 2001 to 2017.…”
Section: Implantable Cardioverter-defibrillatorsmentioning
confidence: 83%
“…A review of data collected from 2006 to 2016 by the existing cardiac implant registries was recently published [7]. Completeness is the "ratio between the number of procedures submitted to the Registry and the number of procedures performed in a specific geographical area" [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed registry characteristics for several topics in cardiology, such as percutaneous coronary intervention (PCI), 1 cardiac implant devices, 14 and transcatheter aortic valve implantations. 15 However, no studies have analyzed cardiac registries across the whole cardiac specialty—the aim of this study.…”
mentioning
confidence: 99%
“…The patient's general cardiologist was aware that this surgery was planned and had determined that no programming changes were needed preoperatively. 1 On the day of surgery, the anesthesiology perioperative CIED service interrogated the ICD and found that it was functioning properly. The interrogation also showed that the patient had an underlying sinus bradycardia with an atrial rate of 55 bpm.…”
Section: Case Reportmentioning
confidence: 99%
“…AN INCREASING number of patients are receiving cardiac implantable electronic devices (CIEDs), and many undergo surgical procedures. 1 Surgical procedures involving the carotid artery, while not associated with major fluid shifts, may be associated with hemodynamic instability resulting from the activation of the baroreceptor reflexes, leading to hypotension and bradycardia. Elderly patients are specifically prone to severe hemodynamic perturbations resulting from the activation of the baroreceptor reflex owing to inherent reduction in the stimulation of beta-receptors and replacement fibrosis of their conduction system.…”
mentioning
confidence: 99%